Renal volumetry and functional impairment prediction in pediatric vesicoureteral reflux based on contrast-enhanced voiding urosonography - Du, Lanxin; Pang, Houqing; Tan, Yifei; Luo, Hong; He, Min (Quantitative Imaging in Medicine and Surgery; Vol 16, No 7 (July 01, 2026): Quantitative Imaging in Medicine and Surgery, 2026)
Background: Contrast-enhanced voiding urosonography (CeVUS) provides a radiation-free alternative for diagnosing vesicoureteral reflux (VUR), but there is limited literature on its utility in evaluating renal volumetric loss and predicting split renal function (SRF) impairment as well as renal scarring (RS). This study aimed to elucidate the impact of VUR and intrarenal reflux (IRR) on renal volume, identify independent risk factors for SRF impairment and RS, and develop a predictive model.Methods: In this retrospective cohort study (from January 2022 to December 2024), 261 children (119 VUR-positive, 142 controls) underwent CeVUS. Renal volume was calculated from two-dimensional (2D) ultrasound measurements using the ellipsoid formula (length × width × depth ×0.523). VUR was graded based on the International Reflux Study Committee criteria (low grade: I–II, moderate grade: III, high grade: IV–V), and IRR was assessed during CeVUS. SRF and RS were evaluated by Tc-99m dimercaptosuccinic acid (99mTc-DMSA) scintigraphy within 2 weeks relative to the CeVUS examination in a subset of patients (n=86). Multivariable logistic regression was performed to identify independent risk factors of SRF impairment and RS.Results: Across VUR grades, renal volume decreased progressively, but only high-grade VUR showed a statistically significant reduction. No significant differences in renal volume were observed among low-grade VUR, contralateral negative, and negative control groups. Among high-grade VUR cases, kidneys with IRR were smaller than those without IRR, though not significantly (P=0.11). IRR predominantly involved the upper poles (cumulative prevalence 83%) and showed strong spatial concordance with both SRF impairment [Jaccard similarity 0.72, 95% confidence interval (CI): 0.65–0.78] and RS (Jaccard similarity 0.69, 95% CI: 0.62–0.75). In multivariate logistic regression analysis, frequent urinary tract infections (UTIs), higher VUR grade, and IRR emerged as independent risk factors for SRF impairment (all P